FROM LEXICAL ACCESS TO HUMOR APPRECIATION: PROCESSING MORPHOPHONOLOGICAL JOKES IN THAI - Parinwattanachoti, Charinwit (วารสารสถาบันวิจัยและพัฒนา มหาวิทยาลัยราชภัฏชัยภูมิ, 2026)
Verbal humor requires readers to recover an intended interpretation from incongruity. However, different linguistic routes may pose different demands on processing and appreciation. While existing literature on verbal humor has focused primarily on nonliteral meaning, less attention has been placed on morphophonological jokes. This study examined humor processing and appreciation among Thai speakers by comparing four types of morphophonological jokes. Thirty native speakers of Thai completed two experiments between July and September 2025. The theoretical interpretation drew on Relevance Theory, the Graded Salience Hypothesis, and Benign Violation Theory, while the joke categories were operationalized using the adapted Dienhart’s (1999) classification of linguistic triggers in punning riddles. Experiment 1 was a lexical decision task designed to establish a baseline for lexical access across morphological-semantic, morphological, semantic, phonological, and control conditions. Experiment 2 was a self-paced reading task using Thai riddles, followed by 10-point appreciation ratings. Reaction times at the critical and spillover regions were analyzed using mixed-effects regression models, whereas appreciation ratings were analyzed using cumulative link mixed models. The models included demographic, cognitive, psychological, and humor-style covariates, together with a participant-level morphological priming index derived from Experiment 1. The lexical decision results revealed facilitation for morphological and morpho-semantic relatedness, indicating sensitivity to lexical and morphological structure. However, in Experiment 2, this baseline priming index did not reliably predict joke-processing reaction times or appreciation ratings. Appreciation ratings stressed a clearer pattern. Homonymy and paraphony were evaluated more favorably than hahaphony, while linguistic perspective contrasts suggested that same-form ambiguity and near-sound resemblance supported appreciation more effectively than polysemy or pseudomorphemic restructuring. By separating baseline lexical facilitation from online joke processing and final appreciation, the study provides experimental evidence that structural differences among Thai morphophonological jokes are more clearly reflected in evaluative judgments than in immediate reading-time costs, highlighting the recoverability of linguistic form as an important feature of humorous reinterpretation.